Effect of block periodization on physical fitness during a competitive soccer season - Mallo, J. (Journal of Quantitative Analysis in Sports, 2012)
This study examined the effect of block periodization on physical fitness in a professional soccer team. Twenty two male players (21.9 ± 2.3 years) were followed in the course of the 2007-2008 season. The season was divided into five training stages which were further subdivided into three consecutive blocks (Accumulation, Transmutation and Realization) where physical workloads focused on a minimal number of capacities. To examine the training volume, time spent developing physical capacities relevant for soccer's match performance was compared within each block. To study training intensity, heart rate was recorded during all training sessions and compared within blocks. Measures of physical characteristics and physical fitness were assessed in every training stage. Time spent performing high-intensity aerobic training was predominant (P<0.001) in Accumulation in relation to Transmutation and Realization blocks. In addition, time devoted to speed endurance training was higher (P<0.01) in Transmutation than in Accumulation and Realization, whereas time spent developing speed was superior (P<0.05) in Realization in comparison to Accumulation and Transmutation. Vertical jumping height and 10-m sprinting time improved (P<0.01) in the last training stage in relation to the initial values. The players covered a 26-30% greater distance (P<0.001) in the yo-yo intermittent recovery level-1 test at the end than at the beginning of the competitive period. These results suggest that block periodization can be an alternative design for soccer training.